Crowdsourcing inspiration: Using crowd generated inspirational stimuli to support designer ideation. (March 2019) - Goucher-Lambert, Kosa; Cagan, Jonathan
Abstract : Inspirational stimuli, such as analogies, are a prominent mechanism used to support designers. However, generating relevant inspirational stimuli remains challenging. This work explores the potential of using an untrained crowd workforce to generate stimuli for trained designers. Crowd workers developed solutions for twelve open-ended design problems from the literature. Solutions were text-mined to extract words along a frequency domain, which, along with computationally derived semantic distances, partitioned stimuli into closer or further distance categories for each problem. The utility of these stimuli was tested in a human subjects experiment ( N  = 96). Results indicate crowdsourcing holds potential to gather impactful inspirational stimuli for open-ended design problems. Near stimuli improve the feasibility and usefulness of designs solutions, while distant stimuli improved their uniqueness. Highlights: 1300 + crowd workers provided written design solutions to problems from the literature. Crowd responses were text-mined to extract near vs. far inspirational stimuli. The utility of extracted inspirational stimuli was tested with a designer cognitive study ( N  = 96). Near inspirational stimuli improve the feasibility and usefulness of solutions. Far inspirational stimuli improve the novelty (uniqueness) of solutions.